Osteomyelitis of the Craniofacial Skeleton - Pincus, David J. (Thieme Medical Publishers, 2009)
Skull-based osteomyelitis, which is a true bony infection, originates from a chronic, inadequately treated infection. Because of the complex craniofacial skeletal anatomy and associated aesthetic concerns, osteomyelitis of the craniofacial skeleton must be uniquely managed and is more difficult to treat than osteomyelitis of other bones of the body. It is thought that osteomyelitis is decreasing in prevalence due to broad-spectrum antibiotic treatment; however, it still remains a challenging clinical entity in developing countries and lower socioeconomic areas.